Src64 controls a novel actin network required for proper ring canal formation in the Drosophila male germline. - Eikenes, Å.H.; Malerød, L.; Lie-Jensen, A.; Sem Wegner, C.; Brech, A.; Liestøl, K.; Stenmark, H.; Haglund, K. (Development, 2015)
In many organisms, germ cells develop as cysts in which cells are interconnected via ring canals (RCs) as a result of incomplete cytokinesis. However, the molecular mechanisms of incomplete cytokinesis remain poorly understood. Here, we address the role of tyrosine phosphorylation of RCs in the Drosophila male germline. We uncover a hierarchy of tyrosine phosphorylation within germline cysts that positively correlates with RC age. The kinase Src64 is responsible for mediating RC tyrosine phosphorylation, and loss of Src64 causes a reduction in RC diameter within germline cysts. Mechanistically, we show that Src64 controls an actin network around the RCs that depends on Abl and the Rac/SCAR/Arp2/3 pathway. The actin network around RCs is required for correct RC diameter in cysts of developing germ cells. We also identify that Src64 is required for proper germ cell differentiation in the Drosophila male germline independent of its role in RC regulation. In summary, we report that Src64 controls actin dynamics to mediate proper RC formation during incomplete cytokinesis during germline cyst development in vivo.